OsEDS1 and OsPAD4 Are Involved in Brown Planthopper Resistance in Rice - Linzhi Fang; Rong Su; Cunyan Li; Xiaodong Liu; Yuanyuan Song; Rensen Zeng; Qiongli Wang; Haitao Cui; Daoqian Chen (Plants)
The crucial roles of the lipase-like protein enhanced disease susceptibility 1 (EDS1) and phytoalexin deficient 4 (PAD4) in disease resistance in Arabidopsis have been identified. However, their function in rice (Oryza sativa L.) resistance to brown planthopper (BPH, Nilaparvata lugens Stål), the most notorious pest of rice, remains unknown. In this study, the transcript levels of OsEDS1 and OsPAD4 were rapidly altered by BPH infestation. Mutation in either OsPAD4 or OsEDS1 resulted in increased rice susceptibility to BPH, which was associated with increased honeydew excretion and an increased host preference of BPH. Furthermore, mutation in either OsPAD4 or OsEDS1 led to decreased basal levels of salicylic acid (SA) and jasmonic acid (JA) in the absence of BPH, along with the depressed expression of the defense-responsive genes OsPAL, OsICS1, OsPR1a, OsLOX1, OsAOS1 and OsJAZ11 involved in SA and JA biosynthesis and signaling. The BPH infestation-mediated elevation of SA levels and the expression of SA biosynthesis and signaling genes was dampened in eds1 and pad4 plants, whereas BPH infestation-mediated depressions of JA levels and the expression of JA biosynthesis and signaling genes were reversed in eds1 and pad4 plants. Taken together, our findings indicated that both OsPAD4 and OsEDS1 positively regulate rice resistance to BPH.